Thyroid gossypiboma: a rare diagnosis with common presentation - Lohani, Kush Raj; Kataria, Kamal; Ranjan, Piyush; Khadka, Sarada; Jayaram, Jnaneshwari (International Surgery Journal, 2019)
Gossypiboma is a surgical negligence and is commonly reported in major abdominal surgeries. It has rarely been reported after thyroid surgeries. We present gossypibomas found in two post-hemithyroidectomy patients who presented differently and at varied time interval after primary surgery. First patient is a middle-aged lady who presented with persistent discharging sinus from neck for the past 4 years. She underwent hemithyroidectomy in the past. Another patient is an elderly lady who presented with lump in the neck for the past 3 months. She also had history of thyroid surgery about 36 years back. With the working diagnosis of thyroid abscess and malignancy in the respective cases, extensive work up was done including imaging and needle aspiration. However, definitive diagnosis could only be made intra-operatively, where gauze piece was found embedded in the prior surgical site. Gossypibomas can present in a varied fashion that can be easily missed from clinical judgement and imaging. High clinical suspicion in patients with prior history of surgery presenting with chronic discharging sinus or lump is key to diagnosing gossypibomas. Safer working environment with safety checkpoints are warranted to avoiding such incidences.